Analisis Penerapan Perencanaan Pajak Final (Final Tax Planning) Melalui Revaluasi Aktiva Tetap Pada PT Astra Internasional Tbk - Erny Pratiwi; Ashar Basyir (Universitas Dian Nuswantoro, 2023)
Fixed asset revaluation is a revaluation of the company's fixed assets resulting from an increase in the value of these fixed assets on the market or due to a low value of fixed assets in the company's financial statements due to devaluation or other reasons, so that the value of fixed assets in the financial statements does not reflect the actual value. reasonable. The purpose of this study is to find out and analyze the application of fixed asset revaluation and planning for tax implementation through fixed asset revaluation of financial reports at PT Astra International Tbk for the 2019-2021 period.In this study, the objects taken were companies engaged in the automotive, financial services, heavy equipment, mining, construction and energy, agribusiness, infrastructure and logistics, information technology, and property sectors, namely PT Astra International Tbk. The type of data used in this study is quantitative data and the source of data obtained is secondary data with data collection techniques using literature and documentation. Then it is processed using descriptive analysis techniques and quantitative analysis by describing the reality that exists at PT Astra International Tbk and comparing it with standard theory so that a conclusion is obtained.Based on the research results, the company has implemented a fixed asset revaluation of its financial statements using the partial revaluation method. Planning for tax implementation through revaluation of fixed assets at PT Astra International Tbk provides changes to the company's income statement, namely savings on the final tax burden. The fixed asset revaluation policy implemented by PT Astra International Tbk has an impact on increasing the book value of fixed assets.